Effects of creatine and carbohydrate loading on cycling time trial performance - Tomcik, K. A.; Camera, D. M.; Bone, J. L.; Ross, M. L.; Jeacocke, N. A.; Tachtsis, B.; Senden, J.; Van Loon, L. J. C.; Hawley, J. A.; Burke, L. M. (Medicine & Science in Sports & Exercise, 2018)
Introduction Creatine (Cr) and carbohydrate loadings are dietary strategies used to enhance exercise capacity. This study examined the metabolic and performance effects of a combined CR and CHO loading regiment on time trial (TT) cycling bouts.